Properties of solid 3He inclusions embedded in crystalline 4He matrix at ultralow temperatures: Low-Temperature Physics and Chemistry in Cryomatrice - Ganshin, A.; Grigor`ev, V.; Maidanov, V.; Mikhin, N.; Penzev, A.; Polev, A.; Rudavskii, E.; Rybalko, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
A study is made of the kinetic properties of the quantum systems formed in dilute solid mixtures of3He in 4He at ultralow temperatures as a result of the first-order phase transition known as phase separation. The system is a crystalline matrix of almost pure 4He in which small solid inclusions of almost pure 3He are embedded. Data on the inclusion growth kinetics, which is governed by diffusion processes in the matrix, are obtained using precise pressure measurements at constant volume. It is shown that impuriton quantum diffusion is the main process causing the inclusion growth at T > 100 mK. At lower temperatures a strong suppression of quantum diffusion is discovered. This suppression can be associated with the elastic strains induced by the large difference in molar volume between the matrix and inclusions. The magnetic relaxation processes in such two-phase crystals are also investigated using a pulsed NMR technique. The spin-lattice and spin-spin relaxation in the inclusions are found to bepractically independent of temperature. This can be described by exchange processes associated with the 3He tunnel motion. The values of the relaxation times are in good agreement with the corresponding times for pure bulk 3He. In contrast with the case of pure solid 3He, the exchange plateau region extends down to lower temperatures. The nuclear magnetic relaxation in the matrix can be described by the Torrey model, which is based on 3He-4He tunnel exchange. The oncentration dependence of the relaxation times coincides with that observed for homogeneous dilute mixtures of 3He in 4He.